Little Red writing - Holub, Joan (Chronicle Books, 2013)
Once upon a time, in pencil school, a brave little red pencil sets out to write an exciting story with nouns and adverbs and everything. But first she has to face the ravenous pencil sharpener, the Wolf 3000.